Guidelines for measuring gender transformative change in the context of food security, nutrition and sustainable agriculture: At a glance - Food and Agriculture Organization of the United Nations; International Fund for Agricultural Development; World Food Programme; CGIAR GENDER Impact Platform (Food and Agriculture Organization of the United Nations, 2023)
In the framework of the EU-RBA Joint Programme on Gender Transformative Approaches for Food Security and Nutrition (JP GTA), FAO, IFAD, WFP and the CGIAR GENDER Impact Platform developed “Guidelines for measuring gender transformative change in the context of food security, nutrition and sustainable agriculture” aimed at enhancing the capacity of research and development partners to design, implement, monitor and evaluate gender transformative interventions. They include step-by-step guidance to formulate qualitative and quantitative indicators and present an overarching framework for measuring gender transformative change. The intended audience of these Guidelines includes gender experts and programme specialists seeking to design, implement, monitor and evaluate gender transformative interventions in food security, nutrition and sustainable agriculture programmes and initiatives. This abbreviated “At a glance” version has been developed as a reference tool to introduce experts and practitioners to key concepts and messages from the Guidelines in a condensed format.